(untitled) (Applied Biological Research, 2020)
Agroforestry is relatively a new name for a set of old practices. The multifarious trees deliberately retained by the farmers on the farm bund form the agroforestry combinations, which supplement the fodder, fuel, fiber, fruits and flosses as their life support system. Grewia optiva is an important fodder tree retained on farm bunds by farmers in Western Himalayan region. The present investigation was aimed to study the effect of G. optiva based traditional agroforestry system i.e. agri-silviculture, on the productivity of bell pepper (Capsicum annuum). The crown spread of tree was considered major factor and categorized into different classes for quantifying its effect on crop growth and production along radial transects from tree trunk. Results revealed that the crown classes significantly affected the yield of bell pepper causing about 33% reduction in yield under tree canopy as compared to the open condition.